EFEKTIVITAS METODE DAKWAH SISTEM LANGSUNG (DSL) DALAM MENANGKAL RADIKALISME PADA MASA PANDEMI COVID-19 - Khaerul Wahidin; Muhammad Azka Maulana; Muhamad Jaenudin; Juhana Juhana (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2020)
This research discusses radicalism in the name of religion that is increasingly emerging in recent decades. The radicalism is growing and grabbing the public's attention. One of them is the case of the recruitment of innocent children and youth in hardline and extreme organizations for purposes that endanger the public. This group of teenagers is usually still psychologically unstable so it is easy to be indoctrinated with incorrect religious teachings and understanding. Looking at the case, the authors was interested in researching the Islamic Youth group Baitul Ma'mur Mosque (RAISMA) Sampora Village, Cilimus District, Kuningan Regency whose coaching system is carried out through the Direct System Da'wah method (DSL). Uniquely, the youth coaching of this mosque continues to survive in the midst of the Covid-19 outbreak, by of course implementing health protocols. The question then: Does the Group of Islamic Youth Baitul Ma'mur Mosque (RAISMA) fall into the category infiltrated by radicalism or vice versa, the silencer? Then, how exactly is DSL model developed and run? This research method uses qualitative approach with literature study analysis. To explore the data, the authors also used data collection techniques through interviews and the dissemination of questionnaires. The data obtained are then arranged regularly and systematically to be analyzed with qualitative approach.